2010
DOI: 10.1093/molbev/msq098
|View full text |Cite
|
Sign up to set email alerts
|

The Enamelin Genes in Lizard, Crocodile, and Frog and the Pseudogene in the Chicken Provide New Insights on Enamelin Evolution in Tetrapods

Abstract: Enamelin (ENAM) has been shown to be a crucial protein for enamel formation and mineralization. Previous molecular analyses have indicated a probable origin early in vertebrate evolution, which is supported by the presence of enamel/enameloid tissues in early vertebrates. In contrast to these hypotheses, ENAM was only characterized in mammals. Our aims were to 1) look for ENAM in representatives of nonmammalian tetrapods, 2) search for a pseudogene in the chicken genome, and 3) see whether the new sequences co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 44 publications
6
48
0
1
Order By: Relevance
“…Consistent with this hypothesis, Sire et al 52 demonstrated that the chicken retains AMELX as a pseudogene. Soon after, Al-Hashimi et al 53 and Quesada et al 54 discovered that the chicken possesses ENAM and MMP20 pseudogenes. Meredith et al 46 48 elaborated on these results, finding ENAM , AMBN , AMTN , AMELX and MMP20 pseudogenes across 48 avian genomes.…”
Section: Amelogenesis Imperfectamentioning
confidence: 99%
“…Consistent with this hypothesis, Sire et al 52 demonstrated that the chicken retains AMELX as a pseudogene. Soon after, Al-Hashimi et al 53 and Quesada et al 54 discovered that the chicken possesses ENAM and MMP20 pseudogenes. Meredith et al 46 48 elaborated on these results, finding ENAM , AMBN , AMTN , AMELX and MMP20 pseudogenes across 48 avian genomes.…”
Section: Amelogenesis Imperfectamentioning
confidence: 99%
“…Further changes following tooth loss Following tooth loss in Neornithes, mutations have accumulated, resulting in the inactivation of genes encoding one specific dentine protein and all three specific enamel proteins; these genes are now pseudogenes in the chicken [6,19]. Therefore, the true teeth obtained through recent mouse mesenchyme-chicken epithelium recombinations [20] are likely to result from contamination by mouse epithelium, because chick epithelium is definitely unable to produce enamel.…”
Section: Diversion Of Gene Functionmentioning
confidence: 99%
“…Since birds became toothless in the Late Cretaceous, several SCPP genes, including DSPP , AMEL , and ENAM , became pseudogenes [Sire et al, 2008;McKnight and Fisher, 2009;Al-Hashimi et al, 2010]. Moreover, no functional P/Q-rich SCPP genes have been identified in birds.…”
Section: Scpp Genes In the Lizard And Bird Genomesmentioning
confidence: 99%